Extraction of Heart Rate from Multimodal Video Streams of Neonates using Methods of Machine Learning - Ferreira, Joana Carlos Mesquita (2020)
The World Health Organization estimates that more than one-tenth of births are premature. Premature births are linked to an increase of the mortality risk, when compared with full-term infants. In fact, preterm birth complications are the leading cause of perinatal mortality. These complications range from respiratory distress to cardiovascular disorders. Vital signs changes are often prior to these major complications, therefore it is crucial to perform continuous monitoring of this signals. Heart rate monitoring is particularly important. Nowadays, the standard method to monitor this vital sign requires adhesive electrodes or sensors that are attached to the infant. This contact-based methods can damage the skin of the infant, possibly leading to infections. Within this context, there is a need to evolve to remote heart rate monitoring methods. This thesis introduces a new method for region of interest selection to improve remote heart rate monitoring in neonatology through Photoplethysmography Imaging. The heart rate assessment is based on the standard photoplethysmography principle, which makes use of the subtle fluctuations of visible or infrared light that is reflected from the skin surface within the cardiac cycle. A camera is used, instead of the contact-based sensors. Specifically, this thesis presents an alternative method to manual region of interest selection using methods of Machine Learning, aiming to improve the robustness of Photoplethysmography Imaging. This method comprises a highly efficient Fully Convolutional Neural Network to select six different body regions, within each video frame. The developed neural network was built upon a ResNet network and a custom upsampling network. Additionally, a new post-processing method was developed to refine the body segmentation results, using a sequence of morphological operations and centre of mass analysis. The developed region of interest selection method was validated with clinical data, demonstrating a good agreement (78%) between the estimated heart rate and the reference.